Subsidiarity v. Pan-europeanism: LGBTQ and Transgender Rights in the EU and under the European Convention of Human Rights - David Schultz (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The European Union and the Council of Europe were supposed to create continent-wide standards and rule for governance, commerce, and human rights. Yet subsidiarity remains an important principle respecting state-specific policy. Occasionally Pan-Europeanism and subsidiarity conflict and this is the case with LGBTQ and transgender rights. This Article examines the legal tensions surrounding the protection of human rights as it addresses transgender individuals and members of the LGBTQ community. It argues that the current framework of law supporting subsidiarity is inconsistent with the broader goals of non-discrimination at the heart of the values of both the European Union and the Council of Europe.